Capabilities assessment to support food systems transformation towards sustainable healthy diets in Ethiopia - Namugumya, Brenda S.; Mengesha, Belay Terefe; Pittore, Katherine; Herens, Marion (International Food Policy Research Institute, 2024)
Collaborative governance processes are increasingly recognized as critical for normative food systems transformation (FST) globally. For instance, collective action and multistakeholder partnerships is one of the main levers of change stated in Ethiopia’s Food Systems Roadmap. The collaborative processes bring together government, private actors, and citizens in collective forums and networks to engage in long-term, goal-oriented decision making and implementation (Ansell and Gash 2008), for example, change towards sustainable healthy diets and better planetary health for all populations. Forming and maintaining collaborative governance processes entail navigating different challenges attributed to the inherently dynamic nature of such partnerships.